Kejadian Diare Bayi 1−12 Bulan dari Perilaku Hidup Bersih dan Sehat (PHBS) Ibu - Grace Watung (Jurnal Sains & Kesehatan, 2022)
Diarrhea is still one of the main causes of illness and death in almost all geographic areas in the world that can affect all age groups, but the highest morbidity and mortality occurs at the age of infants and toddlers. The death figures released by UNICEF last August 2018 show that globally around 2,000 children under the age of five die every day from diarrheal diseases. Of these, most or about 1,800 children per day die from diarrheal diseases due to lack of clean water, sanitation and basic hygiene. This study aims to determine the relationship between Clean and Healthy Behavior and the incidence of diarrhea in infants 1-12 months at the West Passi Health Center. This type of research is quantitative. The research design is descriptive analytic using cross sectional, where the type of research that emphasizes the time of measurement of data is the independent variable of clean and healthy living behavior and the dependent variable is the incidence of diarrhea. Research Results: Based on the results of statistical tests, p value = 0.009, so it can be concluded that there is a relationship between Clean and Healthy Life Behavior and the incidence of diarrhea in infants 1-12 months old at the West Passi Health Center. The dominant mother's PHBS is good and generally does not have diarrhea. Conclusion and Suggestion: For Puskesmas institutions, especially the organizers of the MCH program, to further improve health services for mothers and children to reduce the incidence of infant and child diarrhea.